Biochemical Characterization of GM1 Micelles-Amphotericin B Interaction - Leonhard, Victoria; V. Alasino, Roxana; D. Bianco, Ismael; G. Garro, Ariel; Heredia, Valeria; M. Beltramo, Dante (Current Drug Delivery, 2015)
In this work a thorough characterization of the GM1 micelle-Amphotericin B (AmB) interaction was performed. The micelle formation as well as the drug loading occurs spontaneously, although influenced by the physicochemical conditions, pH and temperature. The chromatographic profile of GM1-AmB complexes at different molar ratios shows the existence of two populations. The differential absorbance of GM1, monomeric and aggregate AmB, allowed us to discriminate the presence of all of them in both fractions. Thus, we noted that at higher proportion of AmB in the complex, increases the larger population which is composed mainly of aggregated AmB. The physical behavior of these micelles shows that both GM1- AmB complexes were stable in solution for at least 30 days. However upon freeze-thawing or lyophilization-solubilization cycles, only the smallest population, enriched in monomeric AmB, showed a complete solubilization. In vitro, GM1-AmB micelles were significantly less toxic on cultured cells than other commercial micellar formulations as Fungizone, but had a similar behavior to liposomal formulations as Ambisome. Regarding the antifungal activity of the new formulation, it was very similar to that of other formulations. The characterization of these GM1-AmB complexes is discussed as a potential new formulation able to improve the antifungal therapeutic efficiency of AmB.
Keywords: gangliosides